Effects of SMYD2‐mediated EML4‐ALK methylation on the signaling pathway and growth in non‐small‐cell lung cancer cells. Issue 6 (22nd June 2017) - Wang, Rui; Deng, Xiaolan; Yoshioka, Yuichiro; Vougiouklakis, Theodore; Park, Jae‐Hyun; Suzuki, Takehiro; Dohmae, Naoshi; Ueda, Koji; Hamamoto, Ryuji; Nakamura, Yusuke
Abstract : A specific subtype of non‐small‐cell lung cancer (NSCLC) characterized with an EML4‐ALK fusion gene, which drives constitutive oncogenic activation of anaplastic lymphoma kinase (ALK), shows a good clinical response to ALK inhibitors. We have reported multiple examples implying the biological significance of methylation on non‐histone proteins including oncogenic kinases in human carcinogenesis. Through the process to search substrates for various methyltransferases using an in vitro methyltransferase assay, we found that a lysine methyltransferase, SET and MYND domain‐containing 2 (SMYD2), could methylate lysine residues 1451, 1455, and 1610 in ALK protein. Knockdown of SMYD2 as well as treatment with a SMYD2 inhibitor in two NSCLC cell lines with an EML4‐ALK gene significantly attenuated the phosphorylation levels of the EML4‐ALK protein. Substitutions of each of these three lysine residues to an alanine partially or almost completely diminished in vitro methylation of ALK. In addition, we found that exogenous introduction of EML4‐ALK protein with the substitution of lysine 1610 to an alanine in these two cell lines reduced the phosphorylation levels of AKT, one of the downstream oncogenic molecules in the EML4‐ALK pathway, and suppressed the growth of the two cell lines. We further showed that the combination of a SMYD2 inhibitor and an ALK inhibitor additively suppressed the growth of these two NSCLC cells, compared with single‐agent treatment. Our results shed light on a novel mechanism that modulates the kinase activity of the ALK fused gene product and imply that SMYD2‐mediated ALK methylation might be a promising target for development of a novel class of treatment for tumors with the ALK fused gene. Abstract : We identified that EML4‐ALK as a novel substrate of the protein lysine methyltransferase SMYD2 and this methylation might play a critical role in the phosphorylation of EML4‐ALK protein and its oncogenic activity. We also imply that the SMYD2 inhibitor might enhance the growth suppressive effect of ALK inhibitors. video abstract